A Study on Constraints in People's Participation in Integrated Watershed Development - Tushar Athare , Baldeo Singh , Vishnu Gouda and B. K. Singh, (Indian Journal of Extension Education, 2013)
A study conducted in Ahmednagar district of Maharashtra, where the famous Anna Hazare's Ralegaon Siddhi was located,a series of constraints were identified in various stages of watershed development process. The major constraints were:lack of agreement on identification and prioritization of felt needs and unfelt needs, lack of conviction among somevillagers to envisage the possible benefits to be accrued through watershed development activities in the initial stage, lackof technically qualified field assistants, inappropriate design of engineering solutions, neglect of technical matters inplanning and design stage, lack of comprehensive understanding of the problem, field situation, appropriate technicalsolutions for watershed by government functionaries in planning stage, procedural delays in approvals, sanctions andfund disbursal, sanctioning power limitations and hierarchy issues, non-availability of funds at the time when mostneeded, and poor quality materials and hence poor quality soil conservation and check dams engineering works in theimplementation stage. In the post-implementation stage, lack of post-implementation budgets for maintenance andsustainable management of watersheds was a major constraint. Among the suggestions given by respondents for betterwatershed management, the most important were: specific measures for human development including good anddedicated leadership, decision by consensus of all stakeholders, encouraging people to take own initiatives and not rely ongovernment for everything, using community pressure for those who do not adhere to group decisions, empoweringwomen with self help groups, and engaging youth in constructive activities. Among the economic and ecologicalmeasures, encouraging dairying to augment farm incomes, banning open grazing, tree felling, undertake massive treeplantation and among the water conservation measures, forming water cooperatives, using water judiciously and arrestingflow of water wherever possible were suggested.